Semiotic Of Sound Technique Impacting the Understanding In Horror Genre Short Film “hawa” (2016) - Teng, Wilynie Miau Le; M. Fazmi Hisham (Penerbit Universiti Malaysia Sabah, 2023)
This study analyses the sound technique that is used to analyse the structure of sound in “Hawa”, Directed by Tan Ce Ding in 2016, a short horror film about a girl who is being locked inside her room by her parents due to her infection. Using semiotic analysis, this research studied their sound technique that they employ to convey a message in each scene. To comprehend how the techniques of various noises used in motion pictures, as well as the temporal evolution of sound energy, create an emotional experience for the audience. In the context of multimedia content analysis and indexing, qualitative methodologies have already been applied to horror film soundtracks. It was decided to use a qualitative research strategy, and more precisely, a hybrid technique that combines thematic analysis with semiotics content analysis. This method was chosen because it was necessary to find, code, classify, and count both obvious and latent meanings in the written responses of the audiences. Thematic analysis is used to analyse the audience’s understanding in Hawa film directed by Tan Ce Ding, that can elicit horror understanding and feeling. Such as the existence of diegetic and non-diegetic sound, contrapuntal sound, parallel sound, and sound bridge can imply to the understanding.